Association between aldehyde dehydrogenase 2 gene rs671 G>A polymorphism and alcoholic liver cirrhosis in southern Chinese Hakka population. Issue 7 (25th May 2021) - Zeng, Dehui; Huang, Qingyan; Yu, Zhikang; Wu, Heming
Abstract: Background: Alcoholic liver cirrhosis (ALC) endangering people's health. The association between aldehyde dehydrogenase 2 (ALDH2) gene polymorphisms and ALC is not clear. To analyze the relationship between ALDH2 and ALC among Hakka population in southern China. Methods: A total of 292 ALC patients and 278 controls were included in the study. The ALDH2 gene rs671 polymorphism was analyzed by polymerase chain reaction (PCR)‐gene chip. Relevant information and medical records of these participants were collected. Results: The ALC patients had higher percentage of smoking, lower prevalence of hypertension, higher level of alanine aminotransferase (ALT), aspertate aminotransferase (AST), alkaline phosphatase (ALP), gamma‐glutamyltransferase (GGT), total bile acid (TBA), total bilirubin (Tbil), and direct bilirubin (Dbil), lower level of total cholesterol (TC), high‐density lipoprotein‐cholesterol (HDL‐C), and low‐density lipoprotein‐cholesterol (LDL‐C) than controls. The proportions of the G/A genotype ( p  = 0.017), G/A plus A/A genotype ( p  = 0.023) and A allele ( p  = 0.031) were significantly higher in ALC patients than that of controls. ALC patients with G/A genotype had higher TC, HDL‐C, and Apo‐A1 than those with G/G genotype, while with A allele had higher HDL‐C, and Apo‐A1 than those with G allele. Logistic regression analysis indicated that ALDH2 SNP rs671 G/A plus A/A genotypes (A allele carriers) (OR 2.030, 95% CI 1.109–3.715, p  = 0.022) in the dominant model was the risk factor for ALC. Conclusions: ALDH2 A allele (G/A + A/A genotypes) increased the risk of developing ALC among Hakka people in southern China. The results should enrich the relevant data and provide valuable information for the future related research. Abstract : Alcoholic liver cirrhosis (ALC) endangering people's health. The association between aldehyde dehydrogenase 2 (ALDH2) gene polymorphisms and ALC is not clear. To analyze the relationship between ALDH2 and ALC among Hakka population in southern China. ALDH2 A allele (G/A + A/A genotypes) increased the risk of developing ALC among Hakka people in southern China. The results should enrich the relevant data and provide valuable information for the future related research.